AlphaII-spectrin is an in vitro target for caspase-2, and its cleavage is regulated by calmodulin binding. - Rotter, Björn (2004)
The spectrin-actin scaffold underlying the lipid bilayer is considered to participate in cell-shape stabilization and in the organization of specialized membrane subdomains. These structures are dynamic and likely to undergo frequent remodelling during changes in cell shape. Proteolysis of spectrin, which occurs during apoptosis, leads to destabilization of the scaffold. It is also one of the major processes involved in membrane remodelling. Spectrins, the main components of the membrane skeleton, are the targets for two important protease systems: m- and micro-calpains (Ca2+-activated proteases) and caspase-3 (activated during apoptosis). In this paper, we show that caspase-2 also targets spectrin in vitro, and we characterize Ca2+/calmodulin-dependent regulation of spectrin cleavage by caspases. Yeast two-hybrid screening reveals that the large isoform (1/L) of procaspase-2 specifically binds to alphaII-spectrin, while the short isoform does not. Like caspase-3, caspase-2 cleaves alphaII-spectrin in vitro at residue Asp-1185. This study emphasizes a role of executioner caspase for caspase-2. We also demonstrated that the executioner caspase-7 but not caspase-6 cleaves spectrin at residue Asp-1185 in vitro. This spectrin cleavage by caspases 2, 3 and 7 is inhibited by the Ca2+-dependent binding of calmodulin to spectrin. In contrast, calmodulin binding enhances spectrin cleavage by calpain at residue Tyr-1176. These results indicate that alphaII-spectrin cleavage is highly influenced by Ca2+ homoeostasis and calmodulin, which therefore represent potential regulators of the stability and the plasticity of the spectrin-based skeleton.